Islamic legal review on the halal certification application procedure for Korean food products - Soediono, Ricardo; Dores, Dedi; Hidayat, A. Taufiq; Sari, Maya Seftya Puspita (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This study aims to examine the halal certification application procedure for Korean cuisine products at LPPOM MUI East Java and assess its legality from the perspective of Islamic law. The research employs a qualitative method with a descriptive-analytical approach. The findings indicate that halal certification aligns with the 1945 Constitution and is supported by legal frameworks such as Law No. 8 of 1999, Law No. 18 of 2012, Law No. 33 of 2014, and Presidential Instruction No. 2 of 1991. Halal certification has become mandatory due to changes in the composition of food, medicine, and cosmetics. The application procedure includes HAS training, implementation of the halal assurance system, document preparation, registration, monitoring, field audits, and certificate issuance.